Biofilm formation and extracellular polymeric substance (EPS) production by Bacillus haynesii and influence of hexavalent chromium. (May 2022) - Maurya, Annapurna; Kumar, Rajesh; Yadav, Pooja; Singh, Anjali; Yadav, Ashutosh; Chowdhary, Pankaj; Raj, Abhay
Highlights: Cr(VI) triggers the thick and sticky EPS layer in the biofilm. Increase in EPS production (10–35%) by B. haynesii after the exposure to Cr(VI). Higher localization of Cr (15.9%) in EPS at 50 mgL -1 of Cr(VI). Maximum reduction of Cr(VI) (27.7 %) by EPS. Abstract: Biofilm-forming bacteria play a key role in the removal of heavy metals including hexavalent chromium [Cr(VI)] from contaminated sites. In this study, biofilm-forming B. haynesii was examined for extracellular polymeric substances (EPS) production and hexavalent chromium [Cr(VI)] reduction potential. Exposure of B. haynesii with Cr(VI) (12.5–100 mg L -1 ) for 48 h enhanced pellicle dry weight (20–24%), cell-size (5.1–23.2%) and cell granularity (8.5–19.2%). Also, EPS production was increased by 10–35% by promoting the synthesis of protein (94–119%) and polysaccharide (2–33%) components in EPS. Further, the reduction (27.7 %) and distribution (15.87%) of Cr(VI) were mainly mediated by EPS than the other cellular fractions. Findings of the study suggest that the EPS from B. haynesii was efficiently reduced to Cr(VI) present in aqueous medium and the potential of the organism can be further explored for the mitigation of Cr(VI) contamination.